Paired Ductal Carcinoma In Situ and Invasive Breast Cancer Lesions in the D-Loop of the Mitochondrial Genome Indicate a Cancerization Field Effect. (26th December 2012) - Maggrah, Andrea; Robinson, Kerry; Creed, Jennifer; Wittock, Roy; Gehman, Ken; Gehman, Teresa; Brown, Helen; Harbottle, Andrew; Froberg, M. Kent; Klein, Daniel; Reguly, Brian; Parr, Ryan
Abstract : Alterations in the mitochondrial genome have been chronicled in most solid tumors, including breast cancer. The intent of this paper is to compare and document somatic mitochondrial D-loop mutations in paired samples of ductal carcinoma in situ (DCIS) and invasive breast cancer (IBC) indicating a potential breast ductal epithelial cancerization field effect. Paired samples of these histopathologies were laser-captured microdissected (LCM) from biopsy, lumpectomy, and mastectomy tissues. Blood samples were collected as germplasm control references. For each patient, hypervariable region 1 (HV1) in the D-loop portion of the mitochondrial genome (mtGenome) was sequenced for all 3 clinical samples. Specific parallel somatic heteroplasmic alterations between these histopathologies, particularly at sites 16189, 16223, 16224, 16270, and 16291, suggest the presence of an epithelial, mitochondrial cancerization field effect. These results indicate that further characterization of the mutational pathway of DCIS and IBC may help establish the invasive potential of DCIS. Moreover, this paper indicates that biofluids with low cellularity, such as nipple aspirate fluid and/or ductal lavage, warrant further investigation as early and minimally invasive detection mediums of a cancerization field effect within breast tissue.